2021
DOI: 10.3390/en14248452
|View full text |Cite
|
Sign up to set email alerts
|

A Characterization of European Collective Action Initiatives and Their Role as Enablers of Citizens’ Participation in the Energy Transition

Abstract: This paper provides novel additional evidence on the characteristics of Collective Action Initiatives (CAIs), investigating their role within the European energy sector. It analyses and presents results of a survey administered in six European countries: the Netherlands, Belgium, Italy, Poland, Estonia, and Spain. CAIs are studied in light of four key dimensions, those being their creation dynamics, the way they are organized, financed, and the activities they undertake. The results presented are also interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For example, Ravazzoli and colleagues explored the potential of social innovation across rural areas in Europe and found that it produced strong positive "cross-sectoral (societal, economic, environmental, and governmental) and multi-level impacts (on individuals, community, and society)" that have significantly "improved the societal well-being, and contributed to the reduction of certain forms of marginality" 18 . Lupi et al 19 write that social innovation in the form of collective action initiatives has served to raise environmental awareness, promoted the mobilization of citizens, and fostered social inclusion. Similarly, the Joint Research Centre of the European Commission writes that social innovation in the energy sector could satisfy human and societal needs while in parallel empowering vulnerable social groups alongside "cultivating civic traditions of trust, equity, and solidarity within and beyond the spatial context on which they occur" 20,21 .…”
mentioning
confidence: 99%
“…For example, Ravazzoli and colleagues explored the potential of social innovation across rural areas in Europe and found that it produced strong positive "cross-sectoral (societal, economic, environmental, and governmental) and multi-level impacts (on individuals, community, and society)" that have significantly "improved the societal well-being, and contributed to the reduction of certain forms of marginality" 18 . Lupi et al 19 write that social innovation in the form of collective action initiatives has served to raise environmental awareness, promoted the mobilization of citizens, and fostered social inclusion. Similarly, the Joint Research Centre of the European Commission writes that social innovation in the energy sector could satisfy human and societal needs while in parallel empowering vulnerable social groups alongside "cultivating civic traditions of trust, equity, and solidarity within and beyond the spatial context on which they occur" 20,21 .…”
mentioning
confidence: 99%
“…While studying previous experiences, Tricarico [10] investigated how Community Energy Enterprises may innovate the governance of the current energy market. Lupi et al [11] suggest that Collective Action Initiatives are intrinsically socially innovative models of implementation characterised by a strong level of citizen involvement and participation, and that they can contribute to the energy transition from technological and social perspectives. Social innovation and the energy transition was also thoroughly discussed by Hoppe and De Vries [12], who acted as editors of a Special Issue of Sustainability, and also by Hewitt et al [13], who analysed community energy initiatives in eight European countries between 1970 and 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Citizens interact with the technical energy systems, since they are both the subject and object of social innovation in the energy society, and they are emerging economic actors in the energy markets. To design and optimise fair, inclusive, and just energy transition pathways, it is a requirement to have suitable policy making, good collaborations between stakeholders, realistic business models, and citizens who play an active role in shaping and accelerating the socio-technological energy transition [10,11].…”
Section: Introductionmentioning
confidence: 99%